Team writing : a guide to working in groups - Wolfe, Joanna. (Bedford/St. Martin's, 2010)
"'Team writing' is a brief guide about how to collaborate to produce a major written document. ... [It] focuses on the role of written communication in teamwork. It teaches students how to use written documentation to manage a team ..."--Preface.